2023
DOI: 10.3390/su15086536
|View full text |Cite
|
Sign up to set email alerts
|

SERVQUAL to Determine Relationship Quality and Behavioral Intentions: An SEM Approach in Retail Banking Service

Abstract: Purpose—The aim of the study was to visualize the impacts of the service quality dimensions under the SERVQUAL model regarding the relationship quality and behavioral intentions of consumers in the retail banking services of Bangladesh. Design/Methodology/Approach—In this study, a structured questionnaire was used to conduct a survey, and 234 valid data samples were collected for the quantitative analysis. The measurement and structural models were used to explore the hypothesized connections among variables u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…In services, some studies recognised the indirect effect of service quality on behavioural intention, mediated by the satisfaction variable [41,46], and a variety of works have even shown that service quality directly influences customer behavioural intention [59][60][61]. In turn, some researchers have also revealed the existence of significant correlations and significant direct effects between the perceived quality and the customer's behavioural intention, in the nautical tourism segment [62], in the domain of sports [63] and education [42,43,45].…”
Section: Perceived Quality and Behavioural Intentionmentioning
confidence: 99%
“…In services, some studies recognised the indirect effect of service quality on behavioural intention, mediated by the satisfaction variable [41,46], and a variety of works have even shown that service quality directly influences customer behavioural intention [59][60][61]. In turn, some researchers have also revealed the existence of significant correlations and significant direct effects between the perceived quality and the customer's behavioural intention, in the nautical tourism segment [62], in the domain of sports [63] and education [42,43,45].…”
Section: Perceived Quality and Behavioural Intentionmentioning
confidence: 99%